Fundamentals of Entrepreneurship ENT300 Business Proposal (Education Toys For Child’s Development) / Noorshaza Rizqin Noordin - Noordin, Noorshaza Rizqin (2019)
As we all know, children development is growing while they are playing or when they do problem-solving activities. When children spend more time on the gadget, this will give negative impact to them. A research from National University said that early childhood education is important because it is when children first learn to interact with others including friends, teachers, parents and start to develop interest that will stay with them throughout their lives.